Project Prioritization Using Fuzzy AHP (FAHP) And 4c Diamond Marketing Model In Digital Wallet Application Development - Tomy Aulia Alfianto; Bustanul Arifin Noer; Jerry Dwi Trijoyo Purnomo (Information Technology and Science (ITScience), 2025)
The rapid growth of digital wallet applications in the financial technology sector has created increasing complexity in strategic decision-making for development project prioritization. This research addresses the challenge of systematically evaluating and prioritizing multiple development projects by implementing the Fuzzy Analytic Hierarchy Process (FAHP) method combined with the 4C diamond model framework. The study focuses on a digital wallet application development case, where ten projects were evaluated against four main criteria: Customer, Company, Competitor, and Change, along with their respective sub-criteria. The methodology employs triangular fuzzy numbers to handle uncertainty and subjectivity inherent in expert judgments, while the 4C diamond model provides a comprehensive framework for strategic analysis. Data collection was conducted through structured interviews with industry experts and stakeholders involved in digital wallet development. The FAHP method was applied to calculate criteria weights and project scores, followed by comprehensive sensitivity analysis to validate the prioritization model's robustness. Results demonstrate that customer-centric factors dominate the decision-making process with the highest weight of 0.425, followed by company considerations (0.323), change adaptability (0.206), and competitive factors (0.046). The final prioritization identified five top-priority projects based on their strategic alignment and value potential. Sensitivity analysis confirmed the model's stability, with ±10% weight variations showing minimal impact on ranking consistency. The research contributes to technology project management by providing a structured, quantitative approach to strategic decision-making in digital financial services. The proposed framework demonstrates applicability beyond digital wallet development, serving as a replicable model for multi-criteria decision-making in technology project prioritization.